The experience of pain and redness in patients with moderate to severe plaque psoriasis. (3rd September 2015) - Martin, Mona L.; Gordon, Kenneth; Pinto, Lionel; Bushnell, Donald M.; Chau, Dina; Viswanathan, Hema N.
Abstract: Introduction : The Psoriasis Symptom Inventory is a patient-reported outcome instrument that assesses severity of psoriasis signs and symptoms. In early qualitative research, patients reported pain related to psoriasis skin lesions and redness of affected areas of skin as key symptoms. Methods : Individual concept elicitation interviews and cognitive interviews were conducted in adults with moderate to severe plaque psoriasis. Interviews were audio-recorded and transcribed. Concepts were identified, coded and grouped by similar content using Atlas.ti software. Results were evaluated using qualitative research methods. Results : Of 30 patients recruited, 20 patients participated in concept elicitation interviews and 10 participated in cognitive interviews. Concept codes for skin pain and descriptions of color comprised 11% and 15%, respectively, of all symptom-related expressions. Of 90 pain-related expressions, 22 were about pain related to unconscious scratching and 68 were about pain from the psoriasis lesions. Of 199 color-related expressions, 72 were about red or reddish lesion color. Patients with darker skin tones were found to interpret redness consistently. Discussion : These results provide further support to content validity of pain and redness concepts in the Psoriasis Symptom Inventory. Conclusions : Symptoms of skin pain and redness are highly relevant to patients with psoriasis.